Benthic habitat mapping and assessment of seagrass species diversity in Da Lon Reef, Truong Sa Islands, Vietnam, using very high-resolution satellite imagery and in situ data - Dang Nguyen, Hoi; Trung Ngo, Dung; Viet Vu, Dung (Vietnam Journal of Earth Sciences, 2023)
Benthic habitats are critical in shallow sea areas; they regulate the diversity and richness of organisms in each area. Mapping benthic habitats elucidates natural sea characteristics and aids in managing and using natural resources, as well as conserving marine biodiversity. This study established a benthic habitat map for the Da Lon Reef area, Truong Sa Islands, Vietnam, using Pléiades high-resolution remote sensing imaging materials and field survey results from 2020 and 2021. We identified seven classes of benthic habitats with a 91.64% overall accuracy, corresponding to a Kappa coefficient of 0.88. In the Da Lon Reef, seagrass biomes occupy a large area (more than 200 ha) and are distributed mainly inside lagoons at depths of 2–6 m. The field survey results identified five seagrass species and the biodiversity and biomass of seagrass populations in the lagoon of Da Lon Reef. The study results confirm the fundamental value of resources, biodiversity in general and seagrass in particular, in managing and protecting shallow sea ecosystems and biodiversity conservation in the Da Lon Reef area, an important part of the Truong Sa Islands, Vietnam.